2016
DOI: 10.1016/j.yjmcc.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac atrial appendage stem cells promote angiogenesis in vitro and in vivo

Abstract: Cardiac atrial appendage stem cells (CASCs) show extraordinary myocardial differentiation properties, making them ideal candidates for myocardial regeneration. However, since the myocardium is a highly vascularized tissue, revascularization of the ischemic infarct area is essential for functional repair. Therefore, this study assessed if CASCs contribute to cardiac angiogenesis via paracrine mechanisms. First, it was demonstrated that CASCs produce and secrete high levels of numerous angiogenic growth factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Although the number of nodes, meshes and tube length were higher in groups exposed to CM, the results were not significant. However, studies have previously reported that CM from different sources of MSCs or their side populations have the ability to promote tube formation [ 5 , 45 , 46 ], mostly through VEGF signaling that plays a pivotal role in EC sprouting and tubular network formation. This was evidenced by a reduction in the tubular perimeters after addition of VEGF and/or FGF neutralizing antibodies [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of nodes, meshes and tube length were higher in groups exposed to CM, the results were not significant. However, studies have previously reported that CM from different sources of MSCs or their side populations have the ability to promote tube formation [ 5 , 45 , 46 ], mostly through VEGF signaling that plays a pivotal role in EC sprouting and tubular network formation. This was evidenced by a reduction in the tubular perimeters after addition of VEGF and/or FGF neutralizing antibodies [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Previously performed experimental studies have well-demonstrated the promoting impact of CPCs on neo-vessel formation in vitro and in vivo. 67,68 For instance, Dougherty et al showed that exosomes derived from human CPCs could significantly enhance the tube formation in bovine aortic endothelial cells (BAECs) under physoxia (5% O 2 ) as compared to those isolated from ECs cultured in 1 and 21% O 2…”
Section: Cardiac Stem/progenitor Cellsmentioning
confidence: 99%
“…Unlike other in vivo models, such as the murine subcutaneous implant, CAM assay is minimally invasive to the chick embryo and hence, considered a refinement model for animal research (KUE et al, 2015). Many studies have used CAM to evaluate tissue repair including studies about osteogenesis (YAN et al, 2016), myocardial regeneration (FANTON et al, 2016) and even induction of angiogenesis using polymer-based constructs (KANCZLER et al, 2007). We also analyzed the acceptability of the CAM assay over the time (Fig 2a).…”
Section: Research Areas Using Cam Assaymentioning
confidence: 99%